Activation of LC3 low-carbon cements by C-S-H seeding. - Morales-Cantero, Alejandro; Gómez-de-la-Torre, María de los Ángeles; Cuesta-García, Ana María; Santacruz-Cruz, María Isabel; Mazanec, Oliver; Dalla-Libera, Alessandro; Dhers, Sebastien; Schwesig, Peter; Borralleras, Pere; García-Aranda, Miguel Ángel (My University, 2023)
Portland-based Limestone Calcined Clay Cements (LC3) are attracting a lot of the attention from scholars and field applications due to the reduction in CO2 emissions. However, their low mechanical strengths at early ages are a key bottleneck for their widespread use. Calcined clays can also lead to a strong reduction of the fluidity in the first hours after mixing, which is an important second drawback. Here, these two issues have been addressed. Three LC3 binders were prepared based on a PC-52.5R cement and three calcined clays, with variable amounts of kaolinite in the raw materials ranging 29-74 wt%. The particle sizes of the calcined clays were adjusted by milling to Dv,50=13±2 μm. The results show that the loss of fluidity of LC3 mortars during the first hours can be solved by a recently developed PCE-based superplasticizer, specifically tailored for this application. Moreover, the compressive strengths at 1 day for LC3 mortars have been boosted by a C-S-H nucleation seeding admixture and the gains are maintained at 28 days. It is noted that the compressive strengths at 1 day and room temperature were increased by 45-100 %, when compared to the corresponding unseeded mortars.
Keywords: Cemento Portland; Arcilla; Calcined clay; Admixtures; Superplasticizer; CO2 footprint; Mechanical strength